Regulated viral BDNF delivery in combination with Schwann cells promotes axonal regeneration through capillary alginate hydrogels after spinal cord injury - Liu, Shengwen; Sandner, Beatrice; Schackel, Thomas; Nicholson, LaShae; Puttagunta, Radhika; Weidner, Norbert; Blesch, Armin (Acta biomaterialia, 2017)
Grafting of cell-seeded alginate capillary hydrogels into a spinal cord lesion site provides an axonal bridge while physically directing regenerating axonal growth in a linear pattern. However, without an additional growth stimulus, bridging axons fail to extend into the distal host spinal cord. Here we examined whether a combinatory strategy would support regeneration of descending axons across a cervical (C5) lateral hemisection lesion in the rat spinal cord. Following spinal cord transections, Schwann cell (SC)-seeded alginate hydrogels were grafted to the lesion site and AAV5 expressing brain-derived neurotrophic factor (BDNF) under control of a tetracycline-regulated promoter was injected caudally. In addition, we examined whether SC injection into the caudal spinal parenchyma would further enhance regeneration of descending axons to re-enter the host spinal cord. Our data show that both serotonergic and descending axons traced by biotinylated dextran amine (BDA) extend throughout the scaffolds. The number of regenerating axons is significantly increased when caudal BDNF expression is activated and transient BDNF delivery is able to sustain axons after gene expression is switched off. Descending axons are confined to the caudal graft/host interface even with continuous BDNF expression for 8 weeks. Only with a caudal injection of SCs, a pathway facilitating axonal regeneration through the host/graft interface is generated allowing axons to successfully re-enter the caudal spinal cord.